دینی سیاسی جماعتوں کے اقدامات کے معاشرتی اثرات :تحقیقی وتنقیدی جائزہ: Social Impacts of the Actions of Religious Political Parties: An Analytical and Critical Study - Muhammad Saleem Sarwar; Prof. Dr. Khalid Mahmood Arif (Corresponding Author) (jihat-ul-islam, 2025)
This study investigates the social impacts of the actions and policies of religious political parties in Pakistan, with reference to Jamaat-e-Islami (JI), Jamiat Ulema-e-Islam (JUI), Jamiat Ulema-e-Pakistan (JUP), Markazi Jamiat Ahl-e-Hadith (MJA) and Tehreek-e-Labbaik Pakistan (TLP). The primary objective of this research is to explore how these parties, through their political, religious and social initiatives, have influenced societal structures, public consciousness, and the religious orientation of the masses. Furthermore, the study seeks to critically examine whether their strategies have contributed to social harmony and reform or, conversely, generated polarization and ideological rigidity. The methodology adopted is qualitative, relying on documentary analysis of party manifestos, speeches, policy documents, and election campaigns. Secondary sources such as scholarly articles, books, and reports on religious politics in Pakistan are also utilized to provide context and critical perspectives. Comparative content analysis is applied to highlight similarities and differences in the approaches of these parties and to trace their practical outcomes in Pakistani society. Key findings indicate that while these parties have played a significant role in preserving Islamic identity, raising awareness about Shariah-based values, and mobilizing communities around religious causes, they have also faced criticism for fostering sectarian divisions, politicizing faith, and at times obstructing democratic processes. The study concludes that a balanced approach—integrating religious values with inclusive political strategies—remains essential for positive and sustainable societal transformation.